Comparing the effects of lycopene and corticosteroids on oral lichen planus: a systematic review and meta-analysis - Paria Motahari; Rana Daliraan; Solmaz Poorzare (Shahrekord University of Medical Sciences, 2023)
Oral lichen planus (OLP) as an inflammatory disease is autoimmune in nature and there is no definitive treatment for it. Currently, topical and systemic corticosteroids have been adopted as the gold standard in the treatment of OLP, which have significant side effects. Nowadays, the tendency towards natural medicines with antioxidant properties as an alternative treatment has increased due to their low side effects. The main purpose of this systematic review and meta-analysis was to focus on comparing the effects of lycopene as an herbal intervention and corticosteroids on OLP in clinical trials. The search using keywords was done through provided databases from PubMed, Web of Science, Google Scholar, and Scopus until March 2023. After removing duplicate articles and screening them according to eligibility criteria, 5 articles remained and were considered for systematic review and meta-analysis. According to the meta-analysis, significant difference was not observed between the lycopene and corticosteroid groups in terms of reducing pain and improving clinical symptoms after treatment. Lycopene was tolerated well and no specific adverse effects were shown. The systematic review results showed the significant effect of lycopene in the treatment of OLP. The results of this meta-analysis can be useful because no significant side effects have been specified for lycopene. Hence, it might be used instead of steroids.